2007
DOI: 10.1080/07388940701468385
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Forgiveness among Kuwaiti Adolescents and Adults

Abstract: The willingness to forgive was examined in a sample of 517 Kuwaiti citizens, aged 12 to 55 years. Participants were instructed first to read a certain number of stories (in which a harmful act was committed against a child) and then to express their willingness to forgive in each case. The stories included four factors: intent to harm, religious proximity, presence/absence of apologies, and cancellation of consequences. A high level of willingness to forgive was observed among the Kuwaitis studies, irrespectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
4
15
0
4
Order By: Relevance
“…As a result, some of the first attempts at studying forgiveness in socio-political contexts addressed only interpersonal forgiveness (e.g. Azar, Mullet & Vinsonneau, 1999;Azar & Mullet, 2001Ahmed, Azar & Mullet, 2007).…”
Section: Examples Of Intergroup Forgivenessmentioning
confidence: 99%
“…As a result, some of the first attempts at studying forgiveness in socio-political contexts addressed only interpersonal forgiveness (e.g. Azar, Mullet & Vinsonneau, 1999;Azar & Mullet, 2001Ahmed, Azar & Mullet, 2007).…”
Section: Examples Of Intergroup Forgivenessmentioning
confidence: 99%
“…Sunni, Maronites, Druzes), in Vinsonneau and Mullet [2001] among a sample of French adolescents from two different cultures (Magrhebi and Eropean), in Girard et al [2002] among a sample of French adults, and in Ahmed et al [2003] among a sample of Kuwaiti adolescents and adults. In all these studies, willingness to forgive was shown to be a function of a weighted sum of these same four factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, some research has shown Kuwaitis to have a high level of willingness to forgive, especially when an apology has been offered (Ahmed, Azar, & Mullet, 2007). This high willingness to forgive has also been found with survivors of the civil war in Lebanon, even across six major religious groups (Azar & Mullet, 2002).…”
Section: Forgiveness In the Middle Eastmentioning
confidence: 95%